Application of constructed wetland for advanced treatment of industrial wastewater - Nguyen Phuoc Dan; Le Thi Minh Tam; Vu Le Quyen; Do Hong Lan Chi (Vietnam Journal of Science, Technology and Engineering, 2020)
An experimental study to use a pilot vegetated submerged bed (VSB) wetland for the advanced treatment of effluent from the central wastewater treatment plant (CWWTP) of an industrial zone was carried out. The pilot VSB wetland included reeds (Phragmites australis), cattail (Typha orientalis), and blank cells in parallel. The constructed wetland was observed to be a suitable measure for wastewater reuse via the high performance of organic matter, turbidity removal, and detoxification. At loading rates of up to 250 kg chemical oxygen demand (COD) ha-1d-1, both cells with emergent plants obtained high efficiency of contaminant removal. Suspended solids (SS) and turbidity removal reached 67-86% and 69-82%, respectively. The COD removal efficiencies of the reed and cattail cells at a loading rate of 130 kg COD ha-1d-1 were 47 and 55%, respectively. At a high loading of 400 kg COD ha-1d-1, the toxicity unit (TU) reduced from 32- 42 to 4.9 and 4.2 in the effluent of the cattail and reed cells, respectively. Especially at loadings of 70, 130, and 185 kg COD ha-1d-1, the effluent TU was less than 3.0, corresponding to a non-toxic level to the ecosystem. The effluent quality met industrial or landscaped wastewater reuse at these loading rates.